Vascular Genetic Variants and Ischemic Stroke Susceptibility in Albanians from the Republic of Macedonia - Kamberi, Bajram; Kamberi, Farije; Spiroski, Mirko (ID Design 2012/DOOEL Skopje, 2016)
Acute first-ever ischemic stroke (FIS) is a heterogeneous, polygenic disorder. The contribution of vascular genetic variants as inherited causes of ischemic stroke has remained controversial.
Keywords: ischemic stroke; vascular genetic variations; association; Republic of Macedonia; Albanians